Drug Utilization Evaluation of Methotrexate in Psoriasis in a Tertiary Care Teaching Hospital - Subrahmanian, Vijeesh Tholur; Gopal, Kannan; Sundaram, Murugan; Ashok, Purnima; Venkata, Satya Sai Minnikanti (Indian Journal of Pharmacy Practice)
Background: Psoriasis is a common inflammatory skin condition which can have profound impact on patient’s quality of life. Moreover, in pharmacotherapy of psoriasis Methotrexate was the first effective systemic drug for psoriasis and remains in clinical use today. The objective of the study was to evaluate the utilization of methotrexate in psoriasis by assessing prescribing pattern, safety, efficacy and its rational use. Methods: It is a prospective, descriptive study conducted for a period of six months in subjects of either sex aged not more than 60years having psoriasis. Methotrexate was initiated in a single weekly intramuscular or oral dose of 2.5- 5 mg (maximum 30 mg). The treatment response was evaluated using Psoriasis Area and Severity Index in all patients at the baseline and then every month till the remission phase of the disease. Results: After treatment with methotrexate 5-15 mg, significant reduction in psoriasis score were recorded when compared to baseline therapy and also there were no significant side effects observed in the psoriatic patients. Conclusion: Use of methotrexate in the treatment of psoriasis in this study population was found to be safe and effective. Significant Psoriasis Area and Severity Index score reduction was observed during each month of therapy.
Keywords: Methotrexate; Psoriasis; Psoriasis Area and Severity Index; Drug interaction